On the Chronology of the Reliefs with Images of Cybele, Hermes and Hecate Found in the Northern Black Sea Coast - Goroncharovskiy, Vladimir (Acta Archaeologica Lodziensia, 2021)
The article is devoted to the reliefs with images of Cybele, Hermes and Hecate from Olbia and the Bosporus, which were recently dated to the first centuries AD. An early Hellenistic limestone relief bearing a similar scene discovered during excavations in Gorgippia (modern Anapa) in 2020, makes it possible to address once again the question of the origin of this subject, and the date of its appearance on the territory of the Black Sea Coast.